From Longing to Tolerance: A Social Network Analysis of Comments on the Rindu Muhammadku YouTube Video - Muhamad Lutfi Habibi; Solluuhiyyah; Muammar Khadafi (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
One of the phenomena that emerged during Ramadan 2024 in Indonesia was the war takjil, the rise of new funny short-video content on social media showing people hunting for food to break the fast. Uniquely, this activity is not only followed by Muslims but also by non-Muslims. This study examines the song Rindu Muhammadku by Haddad Alwi, which often appears in its source content on YouTube, to identify the communication networks formed in the comments during Ramadan 2024 and to examine how these networks can foster mutual respect between religious communities. Through Social Network Analysis using the Netlytic web tool to analyze 2,500 user comments, it was found that the five largest communication networks exhibited diverse, generally positive interactions that emphasized tolerance. The three largest networks featured non-Muslims praising the song; one network showed expressions of pride in being a convert, while the other, although conveying a message of tolerance, sparked discussions that were often unhealthy. This research is expected to encourage further studies on religious and ethnic tolerance, given Indonesia’s diverse ethnic groups.